2018
DOI: 10.1111/ibi.12609
|View full text |Cite
|
Sign up to set email alerts
|

When to measure plumage reflectance: a lesson from Collared FlycatchersFicedula albicollis

Abstract: Sexually selected colour traits of bird plumage are widely studied. Although the plumage is replaced only at one or two yearly moults, plumage colour has long been shown to change between moults. Nevertheless, most studies measure colour weeks to months after the courtship period, typically at nestling rearing, and it is unclear whether these measurements yield relevant data concerning the primary process of sexual selection. Here we analyse repeated spectrometric data taken from male Collared Flycatchers duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Together with other plumage parts, female wing-patch coloration may be associated with some aspects of their own and their partner's current reproductive investment (Laczi et al 2013(Laczi et al , 2017 and with their own and their partner's behaviour during the incubation period (K€ ot el et al 2016). Furthermore, in male Collared Flycatchers, Hegyi et al (2019) found within-individual decline in colour expression from the courtship through to the offspring rearing period.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Together with other plumage parts, female wing-patch coloration may be associated with some aspects of their own and their partner's current reproductive investment (Laczi et al 2013(Laczi et al , 2017 and with their own and their partner's behaviour during the incubation period (K€ ot el et al 2016). Furthermore, in male Collared Flycatchers, Hegyi et al (2019) found within-individual decline in colour expression from the courtship through to the offspring rearing period.…”
mentioning
confidence: 84%
“…2011, Hegyi et al . 2019) and (2) what mechanisms underlie such changes in colour (for UV‐blue see Johnson & Jones 1993, Surmacki et al . 2011; for yellow see Willoughby et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the dynamic dimension of the condition‐signal link has received increased attention for two reasons. First, signal deterioration has been highlighted as a possible condition indicator (Hegyi, et al., 2019; Surmacki et al., 2011). Second, signals have been demonstrated to indicate the trajectory of condition change (Hegyi, et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among plumage coloration, melanin and carotenoid-based traits are known indicators of individual quality (Hill 1991, Vergara & Fargallo 2011; however, the conspicuousness of depigmented patches remains a matter of debate (Tickell 2003, Galván 2008, Lehikoinen et al 2010. White feathers may entail increased aggression or territorial conflicts for the bearer (Hegyi et al 2008), are more degradable than melanized ones, with a greater predisposition to breakage and abrasion (Kose & Møller 1999, Hegyi et al 2019, and are more susceptible to bacteria (Ruiz-de-Casta ñeda et al 2012) or Mallophaga (Moreno-Rueda 2005). Because of these costs, depigmented patches are thought to reflect individual quality (Fitzpatrick 1998) and function as mate choice or status signals (Pärt & Qvarnstr öm 1997, Dale et al 1999, Tör ök et al 2003, Garamszegi et al 2006, Morales et al 2007, Potti et al 2013, Cantarero et al 2017).…”
mentioning
confidence: 99%